STUDY ON FAILURE MODE AND COUNTERMEASURES OF SHEARER PICKS - ZHAO LiJuan; ZHAO MingYang; LIU XuNan (Jixie qiangdu)
In order to improve the efficiency of coal mining and the service life of shearer,the failure mode and the reasons of cutting teeth were analyzed,and the influence caused by cutting tooth failure was described,in view of the selection,research and development design,manufacturing process and use of cutting teeth in different geological conditions,the countermeasures were discussed,and the quality of cutting teeth is improved by means of reasonable selection of the type of cutting tooth,the geometrical parameters,the optimized blade spiral angle,the application of tribology theory,the use of new cutting material,the surface strengthening and the operation of the workers. Which providing reference for the production of cutting teeth.